2008
DOI: 10.1136/adc.2007.117960
|View full text |Cite
|
Sign up to set email alerts
|

Preventing or accelerating emergency care for children with complex healthcare needs

Abstract: We have developed a coordinated approach towards the provision of healthcare for a group of families with diverse severe chronic medical conditions who frequently present to the ED. Through a comprehensive programme including the development of patient-care plans, care coordination and 24-hour mobile-phone access we were able to enhance families' capacities to manage their children's conditions in the community.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
36
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(37 citation statements)
references
References 18 publications
0
36
0
Order By: Relevance
“…CC models in community and health care settings merit further investigation given the supportive findings from this study. 23 The CC groups identified in these analyses represent unique experiences of families with CSHCN, including those 24,25 In 1 study, a majority of CSHCN reported receiving family-centered care.…”
Section: Discussionmentioning
confidence: 96%
“…CC models in community and health care settings merit further investigation given the supportive findings from this study. 23 The CC groups identified in these analyses represent unique experiences of families with CSHCN, including those 24,25 In 1 study, a majority of CSHCN reported receiving family-centered care.…”
Section: Discussionmentioning
confidence: 96%
“…In this issue of Archives of Diseases of Childhood, Sutton and colleagues17 describe an emergency medicine extension programme intended to attenuate the use of emergency-department (ED) services by CSHCN while improving and expediting the care delivered. I offer kudos to the authors and their staff who provided care as part of the Accelerated Care through Emergency (ACE) Program.…”
mentioning
confidence: 99%
“…Sutton and colleagues17 established content validity for their programme through an advisory group with representation from parents, emergency staff, subspecialty medical providers and representatives from their institution with responsibility for home and community care. This led to development of a 24 hours per day, 7 days a week medical telephone service for CSHCN led by nurse coordinators with physician back-up.…”
mentioning
confidence: 99%
“…Previous studies have found increased rates of admission from the PED for children with chronic conditions compared with children without chronic conditions, ranging from 28% to 38% vs 11% to 23% to the hospital and 1% vs 0.03% to the PICU. 15,19,31,32 This is the first study to use a tool to stratify children with chronic conditions by medical complexity and describe associated PED use and disposition. Although our findings about increased utilization with increased medical complexity are unique, they are not surprising.…”
Section: Discussionmentioning
confidence: 99%